Caffeine increases light responsiveness of the mouse circadian pacemaker. (5th September 2014) - van Diepen, Hester C.; Lucassen, Eliane A.; Yasenkov, Roman; Groenen, Inske; Ijzerman, Adriaan P.; Meijer, Johanna H.; Deboer, Tom
Abstract Caffeine is the most commonly used psychoactive stimulant worldwide. It reduces sleep and sleepiness by blocking access to the adenosine receptor. The level of adenosine increases during sleep deprivation, and is thought to induce sleepiness and initiate sleep. Light‐induced phase shifts of the rest–activity circadian rhythms are mediated by light‐responsive neurons of the suprachiasmatic nucleus (SCN) of the hypothalamus, where the circadian clock of mammals resides. Previous studies have shown that sleep deprivation reduces circadian clock phase‐shifting capacity and decreases SCN neuronal activity. In addition, application of adenosine agonists and antagonists mimics and blocks, respectively, the effect of sleep deprivation on light‐induced phase shifts in behaviour, suggesting a role for adenosine. In the present study, we examined the role of sleep deprivation in and the effect of caffeine on light responsiveness of the SCN. We performed in vivo electrical activity recordings of the SCN in freely moving mice, and showed that the sustained response to light of SCN neuronal activity was attenuated after 6 h of sleep deprivation prior to light exposure. Subsequent intraperitoneal application of caffeine was able to restore the response to light. Finally, we performed behavioural recordings in constant conditions, and found enhanced period lengthening during chronic treatment with caffeine in drinking water in constant light conditions. The data suggest that increased homeostatic sleep pressure changes circadian pacemaker functioning by reducing SCN neuronal responsiveness to light. The electrophysiological and behavioural data together provide evidence that caffeine enhances clock sensitivity to light.